An Immunological Perspective: What Happened to Pregnant Women After Recovering From COVID-19? - Zhao, Sijia; Xie, Ting; Shen, Li; Liu, Hong; Wang, Liling; Ma, Xixiang; Wu, Jianli; Yuan, Shuiqiao; Mor, Gil; Liao, Aihua (Frontiers in Immunology, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has been raging around the world since January 2020. Pregnancy places the women in a unique immune scenario which may allow severe COVID‐19 disease. In this regard, the potential unknown effects of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on mothers and fetuses have attracted considerable attention. There is no clear consistent evidence of the changes in the immune status of pregnant women after recovery from COVID-19. In this study, we use multiparameter flow cytometry and Luminex assay to determine the immune cell subsets and cytokines, respectively, in the peripheral blood and umbilical cord blood from pregnant women recovering from COVID-19 about 2 3 months (n=5). Our results showed decreased percentages of Tc2, Tfh17, memory B cells, virus-specific NK cells, and increased percentages of naive B cells in the peripheral blood. Serum levels of IL-1ra and MCP-1 showed a decreased tendency in late recovery stage (LRS) patients. Meanwhile, there was no significant difference in immune cell subsets in the umbilical cord blood. The placentas from LRS patients showed increased CD68+ macrophages infiltration and mild hypoxic features. The inflammatory damage of the placenta may be related to the antiviral response. Since the receptors, ACE2 and TMPRSS2, utilized by SARS-CoV-2 are not co-expressed in the placenta, so it is extremely rare for SARS-CoV-2 to cause infection through this route and the impact on the fetus is negligible.